Development of semolina starch/agar-based intelligent films by incorporating butterfly pea flower anthocyanins to monitor the freshness of prawns - Srisanthiya Saravanan,; Nor Adilah Abdullah,; Nur Nabilah Hasanah,; Ezzat Mohamad Azman,; Nur Hanani Zainal Abedin,; Mohammad Rashedi Ismail-Fitry, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The natural plant-derived pH indicator film which monitors food freshness during storage has gained attention among researchers due to consumer awareness of food quality, freshness, and food safety. This study aims to develop a semolina/agar-based film (S/A) incorporated with anthocyanins from butterfly pea flower extract (BPE) as a freshness indicator for tiger prawns and freshwater prawns during 4 days of storage at 4±1 °C. The semolina/agarbased butterfly pea extract (S/A/BPE) films were developed with different concentrations of BPE (3, 6, and 9%) by casting method. Increasing BPE up to 9% in the S/A film increased the thickness and moisture content, lowering the films’ water permeability. The film also had a smoother surface structure with a darker colour. Different pH solutions (pH 2.0-12.0) also changed the colour of films, depending on the BPE concentrations. The application of S/A/BPE films on tiger prawns and freshwater prawns caused colour changes from dark blue at day 0 (fresh stage) to intense green at day 2 (beginning of spoilage) indicating the spoilage of samples. The pH values of both prawns were gradually increased. However, no major changes were observed in the texture profile analysis. These results indicate that S/A/ BPE film has the potential to be used as a pH indicator film to detect the freshness of prawn samples.